The role of consistency in use of morphosyntactic forms in child-directed speech in the acquisition of Irish, a minority language undergoing rapid language change. Issue 2 (3rd March 2020) - ANTONIJEVIC, Stanislava; MUCKLEY, Sarah Ann; MÜLLER, Nicole
Abstract: Irish is a rapidly changing minority language spoken as the main community language in some areas of the officially Irish-speaking Gaeltacht regions in Ireland. We analyse narratives from 17 parent–child dyads, living in one such area. All children, aged 3–6;4, had high exposure to the local variety of Irish. The input quality was measured by specifying consistency and accuracy of use of morphosyntactic forms in parental narratives directed to their children. The same morphosyntactic forms were analysed in narrative retell by the children. The children produced with high accuracy those forms that the parents used consistently and accurately. For the forms where parents' usage was inconsistent, large variation in the children's usage was observed. The findings suggest that consistency and accuracy in the use of morphosyntactic forms in the parental language is an important factor in language acquisition; however, its influence might be confounded by other factors.